2009
DOI: 10.4049/jimmunol.0803404
|View full text |Cite
|
Sign up to set email alerts
|

Human Liver Dendritic Cells Promote T Cell Hyporesponsiveness

Abstract: The liver is believed to promote tolerance, which may be beneficial due to its constant exposure to foreign Ags from the portal circulation. Although dendritic cells (DCs) are critical mediators of immune responses, little is known about human liver DCs. We compared freshly purified liver DCs from surgical specimens with autologous blood DCs. Liver and blood DCs were equally immature, but had distinct subset compositions. BDCA-1+ DCs represented the most prevalent liver DC subset, whereas the majority of perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
172
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(195 citation statements)
references
References 48 publications
15
172
1
Order By: Relevance
“…Tissue-resident DCs may undergo local conditioning and adapt their function to the surrounding environment. This notion is supported by data on the unique regulatory mechanisms exhibited by intestinal DCs (60) and our prior work highlighting functional differences between freshly isolated human liver and autologous blood DCs (18). Another limitation of our study is that cDC depletion in the CD11c-DTR mouse is not confined to the liver.…”
Section: Figuresupporting
confidence: 51%
See 1 more Smart Citation
“…Tissue-resident DCs may undergo local conditioning and adapt their function to the surrounding environment. This notion is supported by data on the unique regulatory mechanisms exhibited by intestinal DCs (60) and our prior work highlighting functional differences between freshly isolated human liver and autologous blood DCs (18). Another limitation of our study is that cDC depletion in the CD11c-DTR mouse is not confined to the liver.…”
Section: Figuresupporting
confidence: 51%
“…Hepatic DCs have been shown to exhibit tolerogenic properties and are thought to protect the liver from untoward inflammatory responses to foreign antigens entering the portal circulation (17). We recently discovered that freshly isolated human liver DCs exhibit a propensity for IL-10 secretion at baseline and after TLR stimulation (18). Because TLR9 has been implicated as an important regulator of inflammation through its detection of both bacterial and host DNA (19,20), we sought to determine whether TLR9 activation and cDC production of IL-10 were necessary to confer protection against liver I/R injury.…”
Section: Figurementioning
confidence: 99%
“…The relevance of these findings to cirrhosis in humans is important. A recent report found that human liver DCs are composed primarily of BDCA-1 and BDCA-3 subsets and, similar to their murine counterparts, induce tolerogenic T cells responses to antigen and the expansion of Tregs (14). Further work is required in order to characterize the changes in human liver DCs in cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 The little information that is known about human intrahepatic DC function corroborates these general observations. 58,59 Despite the challenges of accessing specimens and extracting cells, a better understanding of how DCs and monocytes function in the intrahepatic environment is important for therapeutic development.…”
Section: Areas Of Further Investigationmentioning
confidence: 99%